1992
DOI: 10.1002/eji.1830220105
|View full text |Cite
|
Sign up to set email alerts
|

The CD56 adhesion molecule is the major determinant for detecting non‐major histocompatibility complex‐restricted cytotoxic mononuclear cells from the intestinal lamina propria

Abstract: In this study, specific antibodies against natural killer (NK) cell surface markers identify these cells to be commonly present in normal intestinal mucosa of inflammatory bowel disease (IBD) and carcinoma patients. Cells expressing the CD56 adhesion molecule were found to be far more abundant than CD16+ cells. Functional studies revealed that cells mediating non-major histocompatibility complex-restricted cytotoxicity (NK activity) in the lamina propria express the CD56 surface antigen, whereas only a minorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
2
13
1
Order By: Relevance
“…2C). Although granular phenotype may suggest cytolytic potential, significant CD56 ϩ T cell cytotoxicity was not detected in our experiments (data not shown) or other studies (37,41).…”
Section: Because Cd56contrasting
confidence: 60%
See 3 more Smart Citations
“…2C). Although granular phenotype may suggest cytolytic potential, significant CD56 ϩ T cell cytotoxicity was not detected in our experiments (data not shown) or other studies (37,41).…”
Section: Because Cd56contrasting
confidence: 60%
“…ϩ or CD56 Ϫ effector T cells) (41). Although depletion experiments suggested a similar effector function for the CD161 ϩ T cell subset, we did not detect consistent effector function for this subset in our coculture experimental setting (data not shown).…”
Section: Cd56 ϩ T Cells Induce Responder T Cell Activationmentioning
confidence: 61%
See 2 more Smart Citations
“…In this study CD-derived LPMCcontained more CD56+ lymphocytes, especially CD3+, CD56+lymphocytes, and UC-derived LPMChad fewer CD3+, CD56+and CD3~, CD56+lymphocytes compared with control cells, when freshly isolated LPMCwere analyzed in the flow cytometry. Van Tol et al also demonstrated that non-MHC restricted cytotoxicity mediated by CD56+ lymphocytes was increased in CD LPMCcompared with UC LPMC (19). Taken together, the numerical alteration in LAKprecursors among mRNAwas enhanced in freshly isolated LPMCfrom the inflamed mucosa with CDthan in control LPMCbut there was no significant difference in IL-2 mRNA levels between the cells from the diseased mucosa with UCand control cells.…”
Section: Discussionmentioning
confidence: 90%